Congenital malformations at birth in 7,922 consecutive deliveries at Patan Hospital, Nepal - Ansari, Imran; Rajbhandari, Rateena; Chilise, Shiva; Shalh, Ganesh; Maskey, Pratistha; Maharjan, Rashmila; Yadav, Rajiv; Manandhar, Biplav; Ansari, Rahil (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Congenital malformations need to be identified and intervened early to save lives and prevent sufferings. Many birth defects have well known incidence/prevalence rates but these have not been studied thoroughly in the local population of Nepal. The current study was undertaken to determine the prevalence of congenital malformation at birth, to classify them systematically, to study risk factors and immediate outcome of the newborn babies afflicted.Methods: This was a cross sectional study. All newly delivered babies were examined carefully for congenital malformation and when detected, the parents were interviewed in detail.Results: Over the 10 months of study period 7,922 babies were delivered out of which 90 were stillborn. The number of babies with malformations was 64 (0.81%). Polydactyli was observed in 12 (19%) babies whereas cleft lip/palate and malformations of ears in seven (11%) each. Musculoskeletal system was affected in 31 (35%) cases and craniofacial in 18 (21%). Nine (14%) mothers had bad obstetric history and eight (13%) had illness/medication during pregnancy.Conclusions: Congenital malformation is a significant cause of morbidity and mortality in Patan hospital. Our findings support many established thoughts like higher rates in stillbirths but also challenge some age-old beliefs like higher rates in babies born to older mothers.